1998
DOI: 10.1023/a:1008220002148
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of seminoma and sarcoidosis: A myth or fact?

Abstract: A patient with a stage II seminoma of the testis was treated with a routine orchidectomy and irradiation. One and a half years later enlarged mediastinal lymph nodes were noted. Additional staging showed no other abnormalities and a mediastinoscopy was performed. The initial histologic examination confirmed the clinically suspected diagnosis of sarcoidosis. However, additional immunohistochemical analysis unexpectedly demonstrated that there was also a microscopic relapse of the testis tumor. The literature co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
1
29
0
6
Order By: Relevance
“…In addition, sarcoid-like reactions may present with various manifestations in regards to the distribution and time course. The adjacent coexistence of tumor cells and sarcoid granulomas in a single organ, as observed in this case, has also been previously reported (3,10). Furthermore, sarcoid-like reactions may occur simultaneously with the causative tumor as well as paradoxically during or even after tumor resolution (11,12).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, sarcoid-like reactions may present with various manifestations in regards to the distribution and time course. The adjacent coexistence of tumor cells and sarcoid granulomas in a single organ, as observed in this case, has also been previously reported (3,10). Furthermore, sarcoid-like reactions may occur simultaneously with the causative tumor as well as paradoxically during or even after tumor resolution (11,12).…”
Section: Discussionsupporting
confidence: 83%
“…Possibly, a sarcoid-like reaction at distant sites may represent micrometastases. Tjan-Heijnen et al reported a case of sarcoid-like reaction in mediastinal lymph nodes that was accompanied by a microscopic relapse of seminoma, which was detected not by the initial histopathological examination but by an additional immunohistochemical analysis (6). In such a case, the sarcoid-like reaction may have been protective against the spread of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, it is possible for a sarcoidlike reaction to encompass micrometastatic disease that can be missed and treatment be withheld. Therefore, adequate material from multiple biopsy sites, a comprehensive pathologic examination and immunohistological analysis are all necessary to avoid potential pitfalls [12].…”
Section: Discussionmentioning
confidence: 99%